Meningkatkan Kemampuan Geometri dengan Media Alam Sekitar Pada Anak Kelompok B Di PAUD Sultan Qaimuddin Kendari - Akhmad Amar Fauzana; Muh. Shaleh (IAIN Kendari, 2021)
This study aims to determine whether there is an increase in geometric ability through natural media in group B students at the Sultan Qaimuddin Early Childhood Education School (PAUD) Kendari. This research is in the form of classroom action research (CAR). Each cycle consists of four stages: the planning stage, the implementation stage, the observation stage, and the reflection stage. The subjects of this study were 15 children of group B at the early childhood education school of Sultan Qaimuddin Kendari for the 2018/2019 academic year, which consisted of 6 boys and 9 girls. The data were collected using observation sheets, documentation and tests. The results determined that the acquisition of geometrical ability completeness values increased at each stage where the acquisition of pre-action was 26.67%, increased to 60% in cycle I activities and achieved 80% in cycle II. In other words, the implementation of activities in improving geometric abilities by using natural media around can be carried out adequately and optimally for group B students of PAUD Sultan Qaimuddin Kendari.Keywords: Geometry, early childhood, nature media